Passive pre-exposure immunization by tixagevimab/cilgavimab in patients with hematological malignancy and COVID-19: matched-paired analysis in the EPICOVIDEHA registry - Francesco Marchesi; Jon Salmanton-García; Caterina Buquicchio; Federico Itri; Caroline Besson; Julio Dávila-Valls; Sonia Martín-Pérez; Luana Fianchi; Laman Rahimli; Giuseppe Tarantini; Federica Irene Grifoni; Mariarita Sciume; et al. (Journal of Hematology & Oncology, 2023)
Abstract Only few studies have analyzed the efficacy of tixagevimab/cilgavimab to prevent severe Coronavirus disease 2019 (COVID-19) and related complications in hematologic malignancies (HM) patients. Here, we report cases of breakthrough COVID-19 after prophylactic tixagevimab/cilgavimab from the EPICOVIDEHA registry). We identified 47 patients that had received prophylaxis with tixagevimab/cilgavimab in the EPICOVIDEHA registry. Lymphoproliferative disorders (44/47, 93.6%) were the main underlying HM. SARS-CoV-2 strains were genotyped in 7 (14.9%) cases only, and all belonged to the omicron variant. Forty (85.1%) patients had received vaccinations prior to tixagevimab/cilgavimab, the majority of them with at least two doses. Eleven (23.4%) patients had a mild SARS-CoV-2 infection, 21 (44.7%) a moderate infection, while 8 (17.0%) had severe infection and 2 (4.3%) critical. Thirty-six (76.6%) patients were treated, either with monoclonal antibodies, antivirals, corticosteroids, or with combination schemes. Overall, 10 (21.3%) were admitted to a hospital. Among these, two (4.3%) were transferred to intensive care unit and one (2.1%) of them died. Our data seem to show that the use of tixagevimab/cilgavimab may lead to a COVID-19 severity reduction in HM patients; however, further studies should incorporate further HM patients to confirm the best drug administration strategies in immunocompromised patients.